Ambivalence, resistance, and alliance ruptures in psychotherapy: it's complicated - Urmanche, Adelya A. (2019)
Ambivalence, resistance, and alliance ruptures are three terms commonly used in psychotherapy, across different theoretical approaches and modalities. However, it is still not clear how those terms are related and how the connection can be used to maintain a therapeutic alliance while addressing clients' ambivalence. This paper aims to briefly describe ambivalence and resistance, describing their impact on psychotherapy process; reintroduce the theory of resistance as a manifestation of ambivalence (Engle & Arkowitz, 2006); and relate it to the concept of alliance ruptures. An original study is presented to further demonstrate this interaction between process and content in psychotherapy sessions. Moreover, this paper will discuss the implications of this relationship, offering directions for psychotherapists in addressing both ambivalence and ruptures in their work.